A new species of Anisandrus Ferrari, 1867 (Coleoptera: Curculionidae: Scolytinae: Xyleborini) from Western China - Lin, Wei; Smith, Sarah M.; Xu, Miaofeng; Li, You (Zootaxa, 2025)
A new ambrosia beetle species of Anisandrus Ferrari, 1867, namely A. tuberculatus sp. nov., is described from Chongqing, Shaanxi and Sichuan of Western China. Descriptions and illustrations are provided based on specimens from type materials found in Yintiaoling Nature Reserve of Chongqing.